1926
DOI: 10.1128/jb.12.1.57-84.1926
|View full text |Cite
|
Sign up to set email alerts
|

Microörganisms Concerned in the Decomposition of Celluloses in the Soil

Abstract: The decomposition of celluloses is carried on in the soil, and in nature in general, by a large number of different organisms. These belong morphologically to the bacteria, the fungi, and the actinomycetes. The organisms decomposing cellulose, especially the bacteria, vary not only in their morphological, but also in their physiological characteristics. The ability to decompose cellulose seems to be widespread among the fungi and actinomycetes, although some fungi are unable to decompose cellulose at all, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1931
1931
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The relatively strongest development of actinomycetes took place in soil + Polyporus, where the colonies of actinomycetes were more than half as numerous as those of the bacteria. These results upon the whole support the opinion expressed by Waksman and Skinner (43), that one of the chief functions of the actinomycetes in the soil is the decomposition of dead microbial, particularly fungal, substance. This agrees well with the fact that actinomycetes nourish abundantly after partial sterilisation of soil (Hiltner and Stormer(i7), Waksman and Starkey (44)).…”
supporting
confidence: 86%
“…The relatively strongest development of actinomycetes took place in soil + Polyporus, where the colonies of actinomycetes were more than half as numerous as those of the bacteria. These results upon the whole support the opinion expressed by Waksman and Skinner (43), that one of the chief functions of the actinomycetes in the soil is the decomposition of dead microbial, particularly fungal, substance. This agrees well with the fact that actinomycetes nourish abundantly after partial sterilisation of soil (Hiltner and Stormer(i7), Waksman and Starkey (44)).…”
supporting
confidence: 86%
“…In the drying processes, fungi, being more tolerant of dryness than bacteria, 28 were likely to have decomposed the cellulose originally contained in the exploited soil. 29 On the other hand, in the less aerobic suspension, bacteria could have contributed to cellulose decomposition rather than fungi. 30…”
Section: Resultsmentioning
confidence: 99%
“…These data emphasize that a short supply of available (inorganic) nitrogen in a soil may restrict the activity of the cellulose decomposing microflora. Other investigators (Jensen, 1931;Waksman and Skinner, 1926;and White et al, 1934) have found that treatments with ammonium or nitrate nitrogen effectively increased the rate of cellulose decomposition in soils. The extent to which the cellulolytic microflora is dependent on inorganic nitrogen in the soil is a question of considerable interest.…”
Section: ]mentioning
confidence: 96%